The possible role furin and furin inhibitors in endometrial adenocarcinoma: A narrative review - Hayder M. Al‐kuraishy; Thabat J. Al‐Maiahy; Ali I. Al‐Gareeb; Athanasios Alexiou; Marios Papadakis; Hebatallah M. Saad; Gaber El‐Saber Batiha (Cancer Reports, 2024)
Abstract Background Endometrial adenocarcinoma (EAC) is a malignant tumor of the endometrium. EAC is the most common female malignancy following the menopause period. About 40% of patients with EAC are linked with obesity and interrelated with hypertension, diabetes mellitus, and high circulating estrogen levels. Proprotein convertase (PC) furin was involved in the progression of EAC. Recent findings Furin is a protease enzyme belonging to the subtilisin PC family called PC subtilisin/kexin type 3 that converts precursor proteins to biologically active forms and products. Aberrant activation of furin promotes abnormal cell proliferation and the development of cancer. Furin promotes angiogenesis, malignant cell proliferation, and tissue invasion by malignant cells through its pro‐metastatic and oncogenic activities. Furin activity is correlated with the malignant proliferation of EAC. Higher expression of furin may increase the development of EAC through overexpression of pro‐renin receptors and disintegrin and metalloprotease 17 (ADAM17). As well, inflammatory signaling in EAC promotes the expression of furin with further propagation of malignant transformation. Conclusion Furin is associated with the development and progression of EAC through the induction of proliferation, invasion, and metastasis of malignant cells of EAC. Furin induces ontogenesis in EAC through activation expression of ADAM17, pro‐renin receptor, CD109, and TGF‐β. As well, EAC‐mediated inflammation promotes the expression of furin with further propagation of neoplastic growth and invasion.